2014
DOI: 10.1186/1471-2164-15-442
|View full text |Cite
|
Sign up to set email alerts
|

Large-effect pleiotropic or closely linked QTL segregate within and across ten US cattle breeds

Abstract: BackgroundThe availability of high-density SNP assays including the BovineSNP50 (50 K) enables the identification of novel quantitative trait loci (QTL) and improvement of the resolution of the locations of previously mapped QTL. We performed a series of genome-wide association studies (GWAS) using 50 K genotypes scored in 18,274 animals from 10 US beef cattle breeds with observations for twelve body weights, calving ease and carcass traits.ResultsA total of 159 large-effects QTL (defined as 1-Mb genome window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
175
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 81 publications
15
175
2
2
Order By: Relevance
“…2012; Saatchi et al . 2014). The association may be explained by an increase in birth weight and length due to the height‐increasing allele, although the authors mentioned other candidate genes.…”
Section: Ncapg‐lcorlmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Saatchi et al . 2014). The association may be explained by an increase in birth weight and length due to the height‐increasing allele, although the authors mentioned other candidate genes.…”
Section: Ncapg‐lcorlmentioning
confidence: 99%
“…In cattle, several major loci including PLAG1 and NCAPG‐LCORL explained more than a third of genetic variance in a breed (Saatchi et al . 2014). In horses, only the LCORL region explained 11% and 18% of the phenotypic variance in Franches‐Montagnes and German Warmblood, respectively (Signer‐Hasler et al .…”
Section: Genetic Architecture For Staturementioning
confidence: 99%
“…Although not reported in Table 3 due to P-values slightly .10 24 ; five other suggestive polymorphisms are located within MAGI1 introns. One of these, at position 36,011,838, is located within a highly conserved region according to a multiple alignment of 36 eutherian mammals (www.ensembl.org).…”
Section: Hard-sweep Signalsmentioning
confidence: 99%
“…Interestingly, the results showed that 47 of 61 candidate genes located in QTL regions were associated with meat and carcass traits, and 11 of 61 candidate genes were reported to be associated with meat and carcass traits on the basis of GWAS data. All these 11 genes were present in the 47 candidate genes in QTL regions associated with meat and carcass traits, including chromosome 8 open reading frame 22, CA8, gamma-glutamyl hydrolase, neuropeptides B/W receptor 1, opioid receptor, kappa 1, PCMTD1, RAB2A, RB1-inducible coiled-coil 1, tocopherol (alpha) transfer protein, leucine rich adaptor protein 1-like, and tyrosinase-related protein-1 (Doran et al, 2014;McClure et al, 2012;Nalaila et al, 2012;Nishimura et al, 2012;Saatchi et al, 2014;Veneroni-Gouveia et al, 2012). These results suggested that the Jinnan breed has high genetic potential for beef cattle breeding.…”
Section: Discussionmentioning
confidence: 99%